Endovascular treatment of tiny ruptured anterior communicating artery aneurysms - Tsutsumi, Masanori (Springer-Verlag, 2008)
INTRODUCTION: Because of its high complication rate, the endovascular treatment (EVT) of anterior communicating artery (ACoA) aneurysms less than 3 mm in maximum diameter remains controversial. We evaluated EVT of tiny ruptured ACoA aneurysms with Guglielmi detachable coils (GDCs). METHODS: We treated 19 ruptured ACoA aneurysms with a maximum diameter of ≤3 mm with GDCs. The pretreatment Hunt and Hess score was grade 1 in four patients, grade 2 in six, grade 3 in six, and grade 4 in three. The patients were clinically assessed before and after treatment and with multiple angiographic follow-up studies. RESULTS: All EVTs were successful; there were no aneurysm perforations or any other treatment-related complications. In five patients older than 80 years the transfemoral approach was difficult, and the direct carotid approach was used. Complete and near-complete occlusion was achieved in 16 patients (84.2%) and 3 patients (15.8%), respectively. Of the 19 patients, 16 (84.2%) were followed angiographically for a median of 38.5 months (range 16–72 months). None demonstrated recanalization of the aneurysm requiring additional treatment. In 15 patients (78.9%) the final outcome was good (modified Rankin scale, mRS, score 0–2), and 3 patients (15.8%) died or suffered severe disability (mRS score 4–6). None of 18 patients who were followed clinically for a median of 39.5 months (range 17–84 months) experienced rebleeding. CONCLUSION: Even tiny ruptured ACoA aneurysms can be safely treated by EVT by expert neurointerventionalists using advanced techniques.